Request of the Spanish government for the technical assistance of the League in the study of measures for providing food supplies for refugees : report - Webster, L. ; Alvarez del Vayo, Julio, 1891- ; Russell, Audrey, Dr.; Bray, Denys, 1875-1951
1938-11-03 017a-0020-008 292/946/17a/20(viii)